VALUE ADDED ANALYSIS OF SALTED FISH PROCESSING IN REBO VILLAGE, SUNGAILIAT DISTRICT, BANGKA REGENCY - Rabecha Maros Framita; Fitri Yunda Sari; Lainatussifa; Yulia Kharisma (AGRIBUSINESS JOURNAL, 2026)
The salted fish processing business is undertaken to enhance the shelf life of fisheries products in the post-harvest stage through processing and preservation methods, as well as to generate profit from the sale of salted fish products. These processing and preservation activities necessitate an analysis of the added value derived from transforming fresh fish into salted fish. This study aims to analyze the value added of processing fresh fish into salted fish in Rebo Village, Sungailiat District, Bangka Regency.  The research method employed is a case study with a census technique covering all salted fish business operators.  There are eight salted fish business operators who serve as respondents, categorized into two groups: large-scale enterprises and small-scale enterprises.Data analysis was conducted descriptively and quantitatively using the Hayami method to calculate the value added generated by processing activities. The results indicate that most fish species processed exhibit high value-added ratios (>40%), including lesi, tamban, ciu, and liban fish, while teri falls in the moderate category The high value added demonstrates that salted fish processing significantly enhances the product's economic value through the difference between output and input values, while also contributing to labor income and entrepreneurial profit. However, the variation in value-added ratios across fish species suggests opportunities for efficiency improvements and innovation, particularly for commodities still in the moderate category. Overall, the salted fish processing business in Rebo Village has strong prospects for development as a local-resource-based agroindustry to improve community income.